Handbook of space technology - Ley, Wilfried; Wittmann, Klaus; Hallmann, Willi (Library of flight, 2009)
Contributions from more than 70 experts in every aspect of space technology. Full colour throughout - with superb illustrations and photography. Foreword by Thomas Reiter, European Space Agency astronaut who spent more than 350 days in space including on the Space Shuttle and International Space Station.